2022
DOI: 10.1037/fam0000905
|View full text |Cite
|
Sign up to set email alerts
|

Pleasure in parenting as a mediator between fathers’ attachment representations and paternal sensitivity.

Abstract: The present study examined the mediating role of pleasure in parenting in the link between fathers' attachment representations and paternal sensitivity among 138 father-infant dyads from a rural part of the southeastern United States. First-time fathers' attachment representations were assessed using the Adult Attachment Interview (AAI) prenatally. Pleasure in parenting-a multidimensional construct assessing positive attitudes and beliefs toward the parenting role-was coded from fathers' interviews at 3 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Considering the aforementioned measurement traditions and the divergent underlying theoretical assumptions, it seems important to evaluate how the empirical research speaks to the extent to which adult attachment style/representations assessed with different approaches may be differentially associated with parenting efficacy. Although adult attachment representations assessed with AAI have been widely associated with parenting behaviors and the overall quality of parenting (Ablow et al, 2013; Aytuglu & Brown, 2021; Leerkes et al, 2015; Madigan et al, 2006; Slade et al, 1999; van IJzendoorn & Bakermans-Kranenburg, 2019; Verhage et al, 2016; Waters et al, 2018; Whipple et al, 2011), research particularly focusing on the link between AAI attachment representations and parenting self-efficacy remains sparse. Only two somewhat relevant studies were identified.…”
Section: Review Of Existing Empirical Research That Is Relevant To Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the aforementioned measurement traditions and the divergent underlying theoretical assumptions, it seems important to evaluate how the empirical research speaks to the extent to which adult attachment style/representations assessed with different approaches may be differentially associated with parenting efficacy. Although adult attachment representations assessed with AAI have been widely associated with parenting behaviors and the overall quality of parenting (Ablow et al, 2013; Aytuglu & Brown, 2021; Leerkes et al, 2015; Madigan et al, 2006; Slade et al, 1999; van IJzendoorn & Bakermans-Kranenburg, 2019; Verhage et al, 2016; Waters et al, 2018; Whipple et al, 2011), research particularly focusing on the link between AAI attachment representations and parenting self-efficacy remains sparse. Only two somewhat relevant studies were identified.…”
Section: Review Of Existing Empirical Research That Is Relevant To Th...mentioning
confidence: 99%
“…For example, spending time in physical contact with the infant has been shown to be effective in promoting fathers’ attention to and accurate perceptions of infant crying signals, especially for fathers with more exposure to early adversities (Riem et al, 2021). Relatedly, there also exists some evidence indicating that fathers’ own secure attachment style/representations are associated with their more sensitive parenting behaviors when interacting with the child in various types of activities (Aytuglu & Brown, 2021; Hazen et al, 2010; McFarland-Piazza et al, 2012; Reisz et al, 2019).…”
Section: Evaluation Of the Potential Utility Of Our Proposed Model Fo...mentioning
confidence: 99%
“…The Paternal Postnatal Attachment Scale (PPAS) is one of the most common measures of the fatherinfant bond and conceptualizes fathers' feelings of bonding across three domains; affection and pride in the infant, pleasure in their interactions, and patience and tolerance in the context of the demands of the role (Condon et al, 2008). Fathers' bonds with infants typically develop over the course of the first postpartum year and indicate a capacity to be a secure and reliable attachment figure (Condon et al, 2013;Aytuglu and Brown, 2022). Although no research, to our knowledge, has investigated associations between a propensity to feel anger (i.e., trait anger) and father-infant bonding, studies have linked state anger (i.e., feeling angry in the moment; Spielberger, 1999) and related constructs to deficits in parent-infant relationships.…”
Section: Introductionmentioning
confidence: 99%